The Solution of Fractional Wave Equation by using Modified Trial Equation Method and Homotopy Analysis Method - Kocak, Zeynep Fidan; Bulut, Hasan; Yel, Gulnur (Amer Inst Physics, 2014)
In this study, we applied the Homotopy Analysis method to the nonlinear fractional wave equation. Then, we executed a comparison between analytical solution obtained by using Modified Trial Equation method and approximate solution obtained via Homotopy Analysis method. Finally, we investigated errors analysis by drawing 3D and 2D graphics of the solution of fractional wave equation for different value of alpha.
10th International Conference on Mathematical Problems in Engineering, Aerospace and Sciences (ICNPAA) -- JUL 15-18, 2014 -- Narvik Univ Coll, Narvik, NORWAY
Keywords: Fractional Wave equation; Homotopy Analysis method; The Modified Trial Equation method